Effects of Tai chi on Cardiovascular Responses and Stress Reduction in Prehypertensive Subjects: A Randomized Clinical Trial - Touraj Hashemi Nosrat-abad; Mansour Bayrami; Hossein Namdar; Khalil Esmaeilpour; Davoud Ezzati (Asociación Española de Ciencias del Deporte, 2021)
Prehypertension seems to be the precursor to hypertension, and using non-pharmacological methods such as tai chi, can reduce blood pressure and its dangerous consequences. Therefore, this study aimed to examine the effects of 8-form Yang-style tai chi on cardiovascular responses and stress reduction in prehypertensive subjects. Sixty prehypertensive men and women aged 25 to 54 years were selected by purposive sampling, and randomly assigned into two experimental groups (15 males and 15 females) and two control groups (15 males and 15 females). Systolic and diastolic blood pressure, and resting heart rate were measured by digital sphygmomanometer and stress was measured using Markham mental pressure inventory. Then, the experimental groups completed tai chi training for 45 minutes, three days per week for 8 weeks, however, the control groups received no intervention. Twenty four hours after completing the training, the dependent variables were re-measured in the study groups. Factorial multivariate analysis of covariance was used for statistical analysis. The results showed that tai chi significantly decreased systolic blood pressure, resting heart rate, and stress in comparison with control group. Our study encourages and supports that a short style of tai chi is an effective way in improving cardiovascular responses and stress in prehypertensive individuals.